2015
DOI: 10.2139/ssrn.2631960
|View full text |Cite
|
Sign up to set email alerts
|

More Integration, Less Federation: The European Integration of Core State Powers

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), created in 1992 and directed by Dr. Brigid Laffan, aims to develop inter-disciplinary and comparative research and to promote work on the major issues facing the process of integration and European society. The Centre is home to a large post-doctoral programme and hosts major research programmes and projects, and a range of working groups and ad hoc initiatives. The research agenda is organised around a set of core themes and is continuously evolving, ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…This also confirms insights coming from large‐scale empirical studies on Commission‐agencies relationships, which found that the ‘Commission stands out as the driving force behind’ the recent ‘agencification policy’, with close ties between relevant DGs and agencies (Egeberg et al ., , p. 624). While the idea of an erosion of the Commission's role and parallel ‘proliferation of EU institutions’ is accepted more and more in the literature (Genschel and Jachtenfuchs, , p. 47), institutional politics is not necessarily a zero‐sum game, particularly in the context of ever expanding Community competences. Exceeding the narrow remit of this article, this seems to neglect the importance of the increasing use of EU institutions outside the remit of EU law (Peers, ), which points to an expanding and not diminished role for traditional EU institutions such as the Commission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also confirms insights coming from large‐scale empirical studies on Commission‐agencies relationships, which found that the ‘Commission stands out as the driving force behind’ the recent ‘agencification policy’, with close ties between relevant DGs and agencies (Egeberg et al ., , p. 624). While the idea of an erosion of the Commission's role and parallel ‘proliferation of EU institutions’ is accepted more and more in the literature (Genschel and Jachtenfuchs, , p. 47), institutional politics is not necessarily a zero‐sum game, particularly in the context of ever expanding Community competences. Exceeding the narrow remit of this article, this seems to neglect the importance of the increasing use of EU institutions outside the remit of EU law (Peers, ), which points to an expanding and not diminished role for traditional EU institutions such as the Commission.…”
Section: Discussionmentioning
confidence: 99%
“…This article analyzes the development of EU agencies by focusing on how they evolve over time, using this phenomenon to examine what sort of EU integration is occurring in migration policy. While in recent years several new frameworks have been put forward to make sense of developments in EU affairs (Genschel and Jachtenfuchs, , p. 42), empirical testing is still in its infancy, and this paper aims at filling that gap mainly through documentary analysis. While commentators and policy‐makers alike are divided as to the effectiveness of the policy measures adopted during 2015 and 2016, students of EU integration might also wonder how to make sense of these same measures through newly established theories.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we find it promising to think about the meaning and transformation of these relations with reference to academic discussions on 'forms of state' and 'core state powers' in the European Union (Caporaso 1996;Genschel and Jachtenfuchs 2016). These debates are usually concerned with how the evolution of the EU fits into longer-term processes of federal state-building and draw attention to the development of specific forms of authority and policy-making capabilities in relation to their member states over time (Richardson 2012).…”
Section: Development Banks In the European Political Economymentioning
confidence: 99%
“…However, we prefer the notion of an 'investment state', which highlights the idea that polities develop a governmental infrastructure promoting investment in specific sectors in the economy either through direct spending or through financial techniques mobilizing other public or private funds. This can possibly surpass the mobilization of national powers to compensate for the lack of EU infrastructural powers, as sketched by Genschel and Jachtenfuchs (2016), and create genuine supranational capacities by allowing other policy actors to 'make use of Europe', accessing new political, institutional and budgetary resources (Woll and Jacquot 2010).…”
Section: Development Banks In the European Political Economymentioning
confidence: 99%
“…In this view, intergovernmentalism is one among several forms of integration and can co-exist with more supranational forms without any zero-sum relationship between the two. More integration may indeed be achieved with more intergovernmentalism (Bickerton et al 2015;Genschel and Jachtenfuchs 2016).…”
Section: Introductionmentioning
confidence: 99%